2015
DOI: 10.1007/82_2015_5006
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Subcellular Localization of Proteins by Bioinformatic Algorithms

Abstract: When predicting the subcellular localization of proteins from their amino acid sequences, there are basically three approaches: signal-based, global property-based, and homology-based. Each of these has its advantages and drawbacks, and it is important when comparing methods to know which approach was used. Various statistical and machine learning algorithms are used with all three approaches, and various measures and standards are employed when reporting the performances of the developed methods. This chapter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 111 publications
0
8
0
Order By: Relevance
“…Further, the protein sequences identified were analyzed for their characteristics such as pI, molecular weight using TAIR (release 10.0; Berardini et al, 2015 ) and TIGR (release 7.0; Kawahara et al, 2013 ) for Arabidopsis and rice respectively. The subcellular localization of the MDC proteins of Arabidopsis was predicted based on SUBA database ( http://suba3.plantenergy.uwa.edu.au/ ) while that of rice was predicted using subCELlular LOcalization predictor (CELLO v. 2.5: http://cello.life.nctu.edu.tw/ ) (Yu et al, 2006 ) and re-confirmed using WoLF PSORT, an advanced protein subcellular localization prediction tool ( http://www.genscript.com/wolf-psort.html ) (Horton et al, 2007 ; Nielsen, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…Further, the protein sequences identified were analyzed for their characteristics such as pI, molecular weight using TAIR (release 10.0; Berardini et al, 2015 ) and TIGR (release 7.0; Kawahara et al, 2013 ) for Arabidopsis and rice respectively. The subcellular localization of the MDC proteins of Arabidopsis was predicted based on SUBA database ( http://suba3.plantenergy.uwa.edu.au/ ) while that of rice was predicted using subCELlular LOcalization predictor (CELLO v. 2.5: http://cello.life.nctu.edu.tw/ ) (Yu et al, 2006 ) and re-confirmed using WoLF PSORT, an advanced protein subcellular localization prediction tool ( http://www.genscript.com/wolf-psort.html ) (Horton et al, 2007 ; Nielsen, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…It is not trivial to determine how similar a pair of proteins has to be in order to infer the possible subcellular localization. Using sequence alignment programs such as BLAST, it is possible to transfer the subcellular localization annotation from the best hit to the query, or in another word to infer subcellular localization from the annotation of homologs which do not necessarily have experimentally known subcellular localization …”
Section: Methodsmentioning
confidence: 99%
“…Sequence‐based methods use co‐ and post‐translational targeting signals, linear motifs detections, amino acid distributions, gapped‐paired, surface or pseudo amino acid compositions to predict the localization from the sequence directly. In contrast, annotation‐based methods use annotations from databases including localization of homologous protein(s), annotated gene ontology terms, functional domains, text information from PubMed abstracts and protein‐protein interactions . The most successful methods use a combination of both the approaches.…”
Section: Introductionmentioning
confidence: 99%
“…In Gram-negative bacteria, the type I, III, IV, and VI secretion pathways function without signal peptides, and in some cases, there is evidence of Nterminal or C-terminal sorting signals [8,13]. In Gram-positive bacteria, there are also a few known pathways (Wss, holin, and SecA2) [13,14]. This paper will discuss prediction of non-classical secretion in eukaryotes only; prediction in bacteria has been described elsewhere [8,14].…”
Section: Introductionmentioning
confidence: 99%
“…In Gram-positive bacteria, there are also a few known pathways (Wss, holin, and SecA2) [13,14]. This paper will discuss prediction of non-classical secretion in eukaryotes only; prediction in bacteria has been described elsewhere [8,14].…”
Section: Introductionmentioning
confidence: 99%